Modern DevOps in practice - Cordell, Cory W. (Packt, 2019)
"Modern DevOps in Practice will introduce you to modern Development Operations (DevOps), how to utilize it in your development environment work with tools (Terraform and Azure DevOps). After this course you'll be able to bring more automation and standardization to the development process, human errors can be significantly reduced and it will be best practices more efficiently shared across teams. Continuous delivery will help you save time setting up and fixing your working environments. Additionally you will learn about the fundamental principles of DevOps and how to transform your team into one that follows the core of DevOps. By the end of this course you will feel comfortable with what DevOps learn how to utilize modern day tools to better ship code and provide high availability environments."--Resource description page